Stroke Neuroprotection: Targeting Mitochondria - Lora Talley Watts; Richard Justin Garling; Reginald Lloyd; Timothy Duong (Brain Sciences, 2013)
Stroke is the fourth leading cause of death and the leading cause of long-term disability in the United States. Blood flow deficit results in an expanding infarct core with a time-sensitive peri-infarct penumbra that is considered salvageable and is the primary target for treatment strategies. The only current FDA-approved drug for treating ischemic stroke is recombinant tissue plasminogen activator (rt-PA). However, this treatment is limited to within 4.5 h of stroke onset in a small subset of patients. The goal of this review is to focus on mitochondrial-dependent therapeutic agents that could provide neuroprotection following stroke. Dysfunctional mitochondria are linked to neurodegeneration in many disease processes including stroke. The mechanisms reviewed include: (1) increasing ATP production by purinergic receptor stimulation, (2) decreasing the production of ROS by superoxide dismutase, or (3) increasing antioxidant defenses by methylene blue, and their benefits in providing neuroprotection following a stroke.